ELECTION CRISIS, LIBERAL DEMOCRACY AND NATIONAL SECURITY IN NIGERIAâ€™S FOURTH REPUBLIC - Ighodalo, Akhakpe (European Scientific Journal, ESJ, 2012)
ï»¿ï»¿The paper analysed the recurring election crisis under liberal democratic system and the threat it poses to national security in Nigeria. One of the major instruments for selecting political officeholders is election. It serves as means of ensuring accountability and mobilization of the citizenry for political participation. Yet, elections in Nigeria have always been characterized by mal-practices such as: election rigging, snatching and stuffing of ballot boxes, political intimidation and assassination prior to, during and after elections. This has often brought unpopular governments to power with the resultant legitimacy crisis, breakdown of law and order and general threat to security. The paper with the use of structure agency theory, argued that elections in which â€œthe winner takes allâ€ is unsuitable for a plural society like Nigeria. Adaptation of the liberal democratic system to suit the countryâ€™s cultural values and peculiarities should lay the basis for people centered development strategies that will empower them to be active participants in policy making and implementation, under a political climate characterized by the rule of law and constitutionalism. Unless these categorical steps are taken, the country may experience another democratic breakdown that will spell doom for the nation-state.